Cladistic analysis reveals polyphyly of Tomarus (Coleoptera: Scarabaeidae: Dynastinae): new classification and taxonomic revision - López-García, Margarita M.; Deloya, Cuauhtémoc (Zootaxa, 2022)
The phylogeny of Tomarus Erichson, 1847 (Coleoptera: Scarabaeidae: Dynastinae: Pentodontini) was explored by parsimony using morphological characters to approach its taxonomic and nomenclature problems. The genus was not supported as a monophyletic group, and the recovered lineages did not match at all any of the previously known classifications. Three different lineages and six monophyletic groups were recovered, which could be treated as independent genera. However, the classification proposed here is as conservative as possible concerning to the creation of many new names and generic taxa. Thus, four genera are now recognized: Euligyrus Casey, 1915 new status (2 species), Ligyrus Burmeister, 1847 revised status (18 species, including Oxygrylius Casey, 1915 new synonymy), Proculigyrus new genus (1 species), and Tomarus Erichson, 1847 revised status (18 species). Three subgenera are recognized for the genus Ligyrus: Anagrylius Casey, 1915 revised status (2 species), Ligyrodes Casey, 1915 revised status (3 species), and Ligyrus revised status (13 species). A complete taxonomic treatment is presented for each genus, including descriptions, keys, and occurrence maps. A revised status is presented for the following species: Ligyrus (Ligyrus) nasutus (Burmeister, 1847), T. amazonicus (Arrow, 1914), and T. gyas Erichson, 1848. Lectotypes are designated for Bothynus neglectus LeConte, 1847, L. amazonicus Arrow, 1914, L. bryanti Rivers, 1891, Scarabeus fossor Latreille, 1813, S. relictus Say, 1825 T. gyas, T. maimon Erichson, 1847, and some synonyms of L. sallaei Bates, 1888 (Ligyrodes propinquus Casey, 1915 and Ligyrodes aztecus Casey, 1915), S. gibbosus DeGeer, 1774 (Bothynus morio LeConte, 1847, L. californicus Casey, 1909, and L. spissipes Casey, 1909), S. relictus (Ligyrodes parviceps Casey, 1915 and Ligyrodes quadripennis Casey, 1915), and S. bituberculatus Palisot de Beauvois, 1811 (Ligyrus maximus Arrow, 1913 and Ligyrus latus Arrow, 1914). Ligyrus patagonus Steinheil, 1874 is a new synonym for L. rubripes Boheman, 1858. Type species are designated for the synonyms Grylius Casey, 1915 and Ligyrellus Casey, 1915. New combinations (new combination) are presented for: Euligyrus ebenus (De Geer, 1774), E. similis (Endrödi, 1968), Ligyrus (Anagrylius) moroni (López-García & Deloya, 2019), L. (Ligyrus) paranaensis (López-García & Deloya, 2019), L. (Ligyrus) peninsularis (Casey, 1915), L. (Ligyrus) spinipenis (Neita & Ratcliffe 2017), and Tomarus amazonicus. Ligyrus (Ligyrus) allonasutus new species is described to include populations of T. nasutus from western Mexico to Panama. Phylogenetic and taxonomic value of mouthparts, elytro-tergal stridulatory apparatus, and male genitalia is discussed along with a description of the biogeographic patterns of distribution for each genus.